Maximum power Point Tracking control of thermoelectric generation system using extremum seeking control method - Twaha, Ssennoga; Zhu, Jie; Maraaba, Luqman; Huang, Kuo; Li, Bo; Yan, Yuying (MDPI, 2017)
This study proposes and implements maximum power Point Tracking (MPPT) control on thermoelectric generation system using extremum seeking control (ESC) algorithm. The MPPT is applied to guarantee maximum power extraction from the TEG system. The work has been carried out through modelling of thermoelectric generator/dc-dc converter system using Matlab/Simulink. The effectiveness of ESC technique has been assessed by comparing the results with those of the Perturb and observe (P&O) MPPT method under the same operating conditions. Results indicate that ESC MPPT method extracts more power than P&O technique, where the output power of ESC technique is higher than that of P&O by 0.47 W or 6.1% at a hot side temperature of 200⁰C. It is also noted that the ESC MPPT based model is almost fourfold faster than the P&O method. This is attributed to smaller MPPT circuit of ESC compared to that of P&O. Hence, ESC MPPT method outperforms the P&O technique.